Performance of the 20 minutes Whole Blood Clotting Test in detection, monitoring and antivenom therapy of West African Carpet viper (Echis romani) envenoming in resource constrained settings in Nigeria. (1st March 2023) - Hamza, Muhammad; Dajel, Titus B.; Abubakar, Saidu B.; Hamza, Auwalu S.; Abdullahi, Hadiza L.; Iliyasu, Garba; Habib, Abdulrazaq G.
Abstract: The 20 minutes Whole Blood Clotting Test (20WBCT) was evaluated in 1541 snakebite patients at 3 hospitals in Nigeria. It was useful in detection, monitoring, guiding antivenom therapy and prognostication of coagulopathy, with initial sensitivity of 84.7% (95%CI:82.7–86.5%) and specificity of 64.3% (95%CI:50.4–76.7%) compared to clinical envenoming. It led to correct decisions regarding administration or withholding antivenom in 97.93% of patients. The proportion of carpet viper ( Echis romani ) envenomed patients who restored clotting rose steadily following effective antivenom therapy. Patients with positive 20WBCT had severer envenoming, required more blood transfusion, had longer hospital stay and derived higher antivenom protection against death from carpet viper. However, there was no association between positive 20WBCT and fatality or complications. Graphical abstract: Image 1 Highlights: There is lack of reliable, standardized, widely available point-of-care test for diagnosis of snakebite envenoming. The 20 min Whole Blood Clotting Test (20WBCT) is used to detect non-clotting blood in carpet viper envenoming in Africa. The 20WBCT is cheap, rapid and simple to perform with good sensitivity and specificity. The 20WBCT is very useful for detection, monitoring of antivenom therapy and prognostication in carpet viper envenoming.